Dynamic Response and Time-Frequency Characteristic of Dangerous Rocks under the Combined Action of Rock Cavity Weathering and Earthquake - Qingyang Ren; Honghua Jin; Xiaokun Ren; Xingxing Zhang (Advances in Civil Engineering)
In order to further reveal the failure mode and dynamic response law of dangerous rocks with different degree of weathering in the rock cavity under the action of earthquake and to provide early warning and forecast for steep slope of dangerous rocks in similar earthquake areas, a typical steep slope of dangerous rock in earthquake area of Sichuan, China, was taken as the research object, after detailed geological survey, and according to the chain development law of dangerous rock, the steep slope of dangerous rock before the earthquake was restored. Based on the 3D particle flow software PFC3D, the dangerous rock was divided into 3 modes according to the degree of weathering of the mudstone rock cavity, and the three-dimensional discrete element dangerous rock model under different modes was established. By introducing the horizontal and vertical two-way coupled seismic waves in Wenchuan, Sichuan, in 2008, the failure evolution process of steep slope of dangerous rock under the action of the horizontal and vertical coupled seismic waves was dynamically simulated, which proved the rationality of the simulation. The frequency spectrum of velocity-time history signal of each rock block in the dangerous rock model was analyzed by MATLAB programming, and the time-frequency characteristics of each dangerous rock model under the action of coupled seismic wave were studied. The research results have important scientific guiding significance and practical value for the dynamic stability evaluation and prediction of such steep slope of dangerous rocks under the combined action of rock cavity weathering and earthquake.